Mechanistic Insights into the Formation of the 6, 10‐Bicyclic Eunicellane Skeleton by the Bacterial Diterpene Synthase Bnd4. (20th September 2021) - Xu, Baofu; Tantillo, Dean J.; Rudolf, Jeffrey D.
Abstract: The eunicellane diterpenoids are a unique family of natural products seen in marine organisms, plants, and bacteria. We used a series of biochemical, bioinformatics, and theoretical experiments to investigate the mechanism of the first diterpene synthase known to form the eunicellane skeleton. Deuterium labeling studies and quantum chemical calculations support that Bnd4, from Streptomyces sp. (CL12‐4), forms the 6, 10‐bicyclic skeleton through a 1, 10‐cyclization, 1, 3‐hydride shift, and 1, 14‐cyclization cascade. Bnd4 also demonstrated sesquiterpene cyclase activity and the ability to prenylate small molecules. Bnd4 possesses a unique D 94 NxxxD motif and mutation experiments confirmed an absolute requirement for D94 as well as E169. Abstract : Enzymatic and mechanistic characterization of Bnd4, a bacterial diterpene synthase and the first terpene synthase known to form the 6, 10‐bicyclic eunicellane skeleton, is reported. Isotope labeling experiments and quantum chemical calculations support the cyclization mechanism for benditerpe‐2, 6, 15‐triene. An unusual DNxxxD motif was found to be essential for cyclization activity.